Wnt-Fzd signaling sensitizes peripheral sensory neurons via distinct noncanonical pathways - Simonetti, Manuela; Agarwal, Nitin; Bali, Kiran Kumar; Niehrs, Christof; Kuner, Rohini (Neuron, 2014)
Wnt signaling represents a highly versatile signaling system, which plays diverse and critical roles in various aspects of neural development. Sensory neurons of the dorsal root ganglia require Wnt signaling for initial cell-fate determination as well as patterning and synapse formation. Here we report that Wnt signaling pathways persist in adult sensory neurons and play a functional role in their sensitization in a pathophysiological context. We observed that Wnt3a recruits the Wnt-calcium signaling pathway and the Wnt planar cell polarity pathway in peripheral nerves to alter pain sensitivity in a modality-specific manner and we elucidated underlying mechanisms. In contrast, biochemical, pharmacological, and genetic studies revealed lack of functional relevance for the classical canonical β-catenin pathway in peripheral sensory neurons in acute modulation of nociception. Finally, this study provides proof-of-concept for a translational potential for Wnt3a-Frizzled3 signaling in alleviating disease-related pain hypersensitivity in cancer-associated pain in vivo.
Gesehen am 07.08.2020